“Sobrevivió […] la imagen judía de la ciudad”. Representaciones literarias de Łódź en dos autores latinoamericanos - Kobyłecka-Piwońska, Ewa (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The paper aims to analyze the representations of Łódź in two short stories byJuan Manuel Torres and one long narration by Eduardo Halfon. Juan Manuel Torres, Mexicanwriter and filmmaker, lived six years in Łódź, where he studied direction in the FilmSchool. His works “El muchacho que mató a la luna” (The Boy who Killed the Moon) and“Al principio de la primavera” (At the Beginning of the Summer) are settled in this city.Eduardo Halfon, a Jewish writer of Guatemalan origins, travelled to Łódź to know hisgrandfather’s life history. “Oh gueto mi amor” is an illustrated chronicle of this journey.